Role of mTORC1 signaling in postnatal microglia activation preceding neurodegeneration in a mouse model for Niemann-Pick disease Type C - Caroline E. Murray; David S. Betancourt-Trompa; Michael S. Martinez; Julia M. Carson; Lindsay J. Walsh; Will C. Remillard; Kayla B. Fordyce; Rohan Reddy; Ileana Soto (PLoS ONE, 2025)
In Npc1 deficient mice, postnatal developmental alterations in cerebellar microglia and Purkinje cells (PCs) are followed by early-onset neurodegeneration. Even in the absence of PC loss, microglia in Npc1nmf164 mice display hallmark features of activation during early postnatal development, including increased proliferation, enhanced phagocytic activity, and morphological changes indicative of an activated state. In this study, we investigated whether mammalian target of rapamycin complex 1 (mTORC1) drives postnatal activation of cerebellar microglia in Npc1nmf164 mice. We found that elevated CLEC7A (Dectin-1) expression and phosphorylation of S6 ribosomal protein (pS6R), a downstream target of mTORC1, co-occurred in microglial precursors within the developing white matter region (dWMR) of wild-type (WT) mice at postnatal day 7 (P7), as well as in neurodegeneration-associated microglia located in the molecular layer (ML) of Npc1nmf164 mice at P60. In contrast, microglia in the WMR of Npc1nmf164 mice at P60 did not show evidence of CLEC7A expression or increased mTORC1 activation. Interestingly, microglial precursors in the dWMR of Npc1nmf164 mice did not exhibit increased mTORC1 activation at P7 but instead showed delayed increased activation at P10. Inhibiting mTORC1 signaling with rapamycin from P10 to P21 reduced both microglial proliferation and soma size in Npc1nmf164 mice. Additionally, rapamycin treatment preserved VGLUT2⁺ presynaptic terminals/axons that innervate PC dendrites and decreased the total volume of CD68⁺ phagosomes per microglial cell, suggesting a reduction in phagocytic activity. However, the volume of VGLUT2⁺ synaptic material per phagosome remained unchanged between vehicle- and rapamycin-treated groups. While rapamycin enhanced myelination in Npc1nmf164 mice, it did not alter microglial phenotypes in the cerebellar WMR, suggesting that mTORC1 signaling does not mediate WMR microglial activation in this model. Together, our findings demonstrate that mTORC1 activation contributes to the aberrant activation of postnatal ML microglia and to early cerebellar pathology in Npc1nmf164 mice.